Action-oriented prospective policy analysis to inform the adoption of a fiscal policy to reduce diet-related disease in the Solomon Islands. Issue 8 (7th April 2021) - Reeve, Erica; Thow, Anne Marie; Namohunu, Salome; Bell, Colin; Lal, Anita; Sacks, Gary
Abstract: Fiscal tools are recommended as a part of a comprehensive approach to diet-related disease prevention, however, widespread adoption has been hampered by political and economic resistance. The aim of this study was to support an advocacy coalition in the Solomon Islands with evidence-based consideration of the development and implementation of a tax on sugar-sweetened beverages (SSBs), sensitive to local contextual factors and constraints. In 2017–19, we conducted a prospective policy analysis, including document analysis and qualitative interviews with key stakeholders to elicit policy-relevant data, a quantitative analysis to frame the policy problem and examine appropriate implementation mechanisms, and economic modelling to outline the potential benefits associated with different proposed policy solutions. Applying an action-oriented approach to prospective policy analysis enabled us as researchers to engage in the needs of a 'pro-SSB tax' advocacy coalition and prepare them to exploit policy opportunities created by the meeting of policy 'streams'. Our analysis demonstrated that SSBs were being consumed in relatively large amounts, especially by children, and that there were likely to be substantial health and economic benefits associated with a SSB tax. Increasing fiscal uncertainty for key sectors had created an environment prime for the advocacy coalition to pursue the adoption of an SSB tax. However, we found that policymakers face a number of practical challenges in securing effective adoption and implementation of global food policy recommendations, including that it is difficult to demonstrate the potential efficacy of interventions in the local context. The development of a policy package based on local factors resulted in a policy product that was likely to be more persuasive for local policymakers and policy leaders. We suggest that there is substantial scope for researchers to more effectively engage with policy advocates to inform and shape real-world health policy improvements.